Digital Marketing Strategies and Their Impact on Customer Satisfaction and Brand Loyalty - Tiurida Lily Anita; Maidar Simanihuruk; Yuviani Kusumawardhani; Lianna Wijaya (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines how digital marketing strategies influence customer satisfaction and brand loyalty in four-star hotels in Jakarta, Indonesia. Using a quantitative approach with the SEM-PLS method, the research analyzed responses from 330 hotel guests. The study investigated key variables including service quality satisfaction, digital engagement, social media engagement, online presence perception, and digital promotions. Findings show that service quality, online presence perception, promotion effectiveness, and social media engagement significantly affect customer satisfaction with digital marketing. However, digital engagement and digital promotions showed no significant effect. Moreover, customer satisfaction with digital marketing was not found to have a significant influence on brand loyalty. These findings suggest that while digital strategies can enhance satisfaction, they do not automatically translate into loyalty. Hotel managers are encouraged to strengthen service quality and digital credibility to improve guest experience. This research contributes to understanding the effectiveness of digital marketing practices in the hospitality industry and provides practical guidance for enhancing customer interaction and satisfaction.